Self-efficacy and user behavioral intention to use online consultation management system - Mohamad Rahimi Mohamad Rosman; Mohammad Azhan Abdul Aziz; Mohd Akmal Faiz Osman; Noor Masliana Razlan (International Journal of Evaluation and Research in Education (IJERE), 2022)
A consultation is an act of discussing a certain issue between two or more parties. Consultation is considered very important especially in the context of higher education. The Novel Coronavirus 2019 (COVID-19) pandemic has shifted the education paradigm into digital dependency, including consultation management between students and academicians. However, a lack of studies has been conducted on the roles of self-efficacy towards user behavioral intention to use online consultation management systems in the aftermath of a pandemic. Therefore, the purpose of this research is to investigate the relationship between self-efficacy and user behavioral intention to use an online consultation management system. In terms of respondents, 270 students were selected based on convenience sampling. Findings were analyzed using statistical package for social sciences (SPSS) version 26 and SmartPLS version 3.2.8. Hence, this research revealed that proposed hypotheses were all supported. Self-efficacy has a positive and significant relationship with perceived usefulness and perceived ease of use. On the other hand, both perceived usefulness and ease of use were found positively influence attitude towards using online consultation management system.